Rintisan Peradaban Manusia - Faozan Sodik (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2015)
Adam is the first human being created by God as the forerunner of all human descendants. However, the existence of Adam as the first human was often invoked by various scientific views. This paper describes the existence of Adam as., the first human to pioneer the history of human civilization. Through Adam whose position as a Prophet gave a sign that this universe was indeed intended by Allah Almighty to be inherited by those who believed. Adam’s position as a prophet at the same time shows how great the mercy of Allah Almighty which bestows upon various gifts not only physical, but spiritual and meaningful. This is because the early civilization of man was filled with the achievements of non-material civilization in the form of the teachings of the religion of God intended for humans to live their lives in the world.